Cyperaceae of Dehra Dun Valley and the Adjacent Siwaliks - Deva, Som; Naithani, H. B. (Indian Forester, 1974)
This work deals with the Cyperaceae of Dehra Dun Valley and the adjacent Siwaliks covering an area of 2290 sq km between 300 to 1000 m. R.N. Parker (1929) enumerated 30 species and 4 varieties belonging to 12 genera from this area, while the present list gives an 90 species 2 sub-species belonging to 10 genera.